Retrospective Price Indices and Substitution Bias - Walter Erwin Diewert; Marco Huwiler; Ulrich Kohli (Swiss Journal of Economics and Statistics, 2009)
The consumer price index (CPI) is usually computed as a fixed-weighted Laspeyres price index, with the weights updated at discrete intervals only. It is well known that the Laspeyres functional form entails a substitution bias. One way to reduce it would be to use chained indices, and superlative ones if possible. Unfortunately, the necessary data are often missing. This paper proposes a simple method to retroactively compute the CPI once updated weights become available. The proposed index has the Fisher form. This makes it possible to assess the size of the substitution bias. An application to Swiss data is provided.
Keywords: C43; E31; 330; Price index; inflation; superlative indices; substitution bias